ANALISIS WAKTU TEMPUH PERJALANAN KENDARAAN RINGAN KOTA SAMARINDA (STUDI KASUS: JALAN Dr.SOETOMO – PAHLAWAN – KUSUMA BANGSA – KH.AGUS SALIM – BASUKI RAHMAT II – AWANG LONG) - DEWI WULANDARI (KURVA MAHASISWA, 2015)
Time travel (Travel Time) defined the total time required for passing through a certainpath length, including time stops and delays at intersections. And the Vehicle Operating Costs(VOC) is a value that states the amount of costs incurred for the operation of a vehicle undernormal conditions for a particular purpose. The growth of road traffic in the region, especially thecity of Samarinda on roads Dr.Soetomo - Pahlawan - Kusuma Bangsa - KH. Agus Salim - BasukiRahmat II - Awang Long continued to increase rapidly due to the growth and development of thecity as well as the rate of population. In the urban transport system in the region of Samarinda,level of activity, including areas with a high level of activity, such as trade in services andschools, so it is often a conflict of movement of traffic that causes congestion. The method used fordata collection of travel time with a stopwatch, while the data for the analysis of travel time andspeed using MKJII, while the operational costs of vehicles using the PCI (Pacific ConsultantInternational). From the results of calculations can be concluded that there is a late travel time onroads Dr.Soetomo Travel Time 124.892 seconds and with a speed of 22.96 km / h and vehicleoperating costs Rp. 5.260 km.